Development of Web-based Single Channel Multi Steps Online Queuing System with Model View Controller - Darmayunata, Yuvi; Devega, Mariza; Yuhelmi , Yuhelmi (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Abstract: Improvement in service quality will be directly proportional to customer satisfaction. One form of improving the quality of services provided by a Government Institution engaged in the Health sector, namely the Health Center is an effective and efficient queue. This research is a follow-up research where previously an analysis and design of an online queuing system has been carried out. This study aims to make it easier for patients to take queue numbers in advance through the queue website, and patients can come based on a predetermined estimated time. This of course can minimize patient waiting time and also prevent the accumulation of patients in the waiting room of the puskesmas. Single Channel Multi Steps is one of four types of queues and is the type of queue currently running at the Siak Hulu I Kampar-Riau Health Center, while the Model View Controller (MVC) was chosen because it is a feature that makes it easy to create a Web-based application.